Variation in content of tyramine, histamine, 2‐phenylethylamine, tryptamine and their precursor amino acids in a Chardonnay wine by using different commercial active dry yeasts and nitrogen sources. (7th August 2019) - Bordiga, Matteo; Guzzon, Raffaele; Larcher, Roberto; Travaglia, Fabiano; Arlorio, Marco; Coïsson, Jean Daniel
Summary: Wine is a fermented beverage that could be affected by high concentrations of biogenic amines, thus altering organoleptic and health properties. In this work, the capacity of different selected yeast strains regarding to affect the content of tyramine, histamine, 2‐phenylethylamine, tryptamine and their precursor amino acids (pAA) during fermentation has been described. Overall, biogenic amines (BAs) and pAA contents appeared significantly related both to the strain and to the nutrient supplementation applied. Among BAs, without and (with) nitrogen source addition, the concentrations covered a range between 0.1 and 9.5 (0.1–10.3) mg L −1 for tyramine; 0.1 and 4.4 (0.1–4.6) mg L −1 for histamine; 0.4 and 1.1 (0.4–1.4) mg L −1 for 2‐phenylethylamine; and 0.02 and 0.14 (0.01–0.12) mg L −1 for tryptamine, respectively. Considering that also wine yeast species are responsible for BAs formation, the evidence from fermentation trials underlined the relevance of a careful choice of ADY strains and nitrogen sources in the management of alcoholic fermentation in wine. Abstract : The capacity of different selected yeast strains regarding to affect the content of tyramine, histamine, 2‐phenylethylamine, tryptamine and their precursor amino acids (pAA) during fermentation has been described. Biogenic amines (BAs) and pAA contents appeared significantly related both to the strain and to the nutrient supplementation applied.